Traditional Herbal Treatment for Plasmodium Falciparum: A Systematic Review on Traditional Plants to Treat Malaria in Iran - Mehravaran, Ahmad; Mirahmadi, Hadi; Mohamadi, Leili; Dahmardeh, Hamid (International Journal of Psychosocial Rehabilitation, 2020)
Background and Objective: Malaria is a vector-borne disease of global importance, with the vast majority of its life-threatening cases caused by infection with Plasmodium falciparum parasites. A marked decrease in malaria-related deaths worldwide has been attributed to the administration of effective antimalarials against Plasmodium falciparum. Considering the great potential of Iran in terms of plant biodiversity, rich traditional knowledge and practice, and malaria endemicity in the southeast of Iran. The present systematic review attempted to explore, synthesize, and compile medicinal research findings on antimalarial plants in Iran.Material and Method: The searches were conducted by three independent researchers to find the relevant studies published from January 1999 until the end of December 2018. We searched for published literature in the English language in MEDLINE via PubMed, EMBASE™ via Ovid, the Cochrane Library, and the TRIP database. The keywords used in the search strategy were malaria, Plasmodium falciparum, herbal medicine, traditional medicine, antimalaria treatment, and anti-parasitic herbs.Results: Detailed findings from five studies identified a total of forty-one different plant species used in traditional malaria treatments throughout Iran. Khouzestan province represents the most antimalarial species, followed by Golestan. Aerial parts and flowers were the most frequently used plant parts. Six plants, including Citrullus colocynthis, Buxus hyrcana, Physalis alkekengi, Glycyrrhiza glabra, Glycyrrhiza glabra, and Ferula oopoda, showed more antiplasmodial activity than others, with IC50 values ranging from 2.01 to 26.6 μg/mlst K1 (chloroquine-resistant) or 3D7 (chloroquine-sensitive).Conclusion: The investigated medicinal plants gathered in this article as a systematic review could be a key to identifying the compounds with antimalarial effects.